Analysis of Pepper Sales Level in Bangka Belitung: Social Media and E-Commerce Through Marketing Performance - Varikah Khoirunnisa; Afrizal Afrizal; Juhari Juhari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the influence of social media and e-commerce on the marketing performance and sales levels of Bangka Belitung white pepper products, with marketing performance acting as a mediating variable. The research employs a quantitative approach and uses Partial Least Squares–Structural Equation Modeling (PLS-SEM) to analyze data collected from local micro, small, and medium enterprises (MSMEs). The results indicate that social media has a significant positive effect on both marketing performance and sales levels, both directly and indirectly, highlighting its effectiveness as a marketing tool. This is attributed to its ease of access, wide reach, cost efficiency, and interactive capabilities, which enable MSMEs to engage directly with consumers and expand their market presence. In contrast, e-commerce does not demonstrate a significant impact on either marketing performance or sales levels. This lack of effect is likely due to limited adoption among MSMEs, who perceive e-commerce platforms as less practical because of registration complexities, associated fees, and concerns regarding consumer trust and payment security. The study suggests that while social media can be leveraged effectively for marketing Bangka Belitung white pepper, greater awareness, training, and support are needed to increase MSMEs’ engagement with e-commerce to enhance their overall sales and competitive performance in the digital market.